PENGARUH PENERAPAN MODEL PROCESS ORIENTED GUIDED INQUIRY LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI BANGUN RUANG KELAS V SD COKROAMINOTO IKHWAN - Huljannah, Miftha; Saptogani, Rismawati G.; Otaya, Lian Gafar (DIRASATUL IBTIDAIYAH, 2024)
AbstractThis research aims to determine the effect of implementing the Process Oriented Guided Inquiry Learning (POGIL) model on students' mathematics learning outcomes in geometric material. The Process Oriented Guided Inquiry Learning model is expected to improve student learning outcomes. This research uses a Quasi Experimental Design research method with a quantitative research type. The results of this research indicate that there is an influence of the application of the Process Oriented Guided Inquiry Learning model on the learning outcomes of fifth grade students at Cokroaminoto Ikhwan Elementary School. This can be seen from the calculation results obtained t_count = 4.145 and then consulted with a significance level of 0.05 to obtain a t_table value = 2.035. From the results of the average values, it was found that the average value for the experimental class was 92.24, while the average value for the control class was 75.53. Because t_count t_table (4.145 2.035) then Hₒ is rejected. So it can be concluded that there is an influence of the application of the process oriented guided inquiry learning model on mathematics learning outcomes for class V classroom materials at Cokroaminoto Ikhwan Elementary School. Keywords: POGIL Model, Learning Outcomes, Mathematics.